Techno-economical study of solar water pumping system: optimum design, evaluation, and comparison - Kazem Hussein A. (EDP Sciences, 2021)
Solar water pumping systems are fundamental entities for water transmission and storage purposes whether it is has been used in irrigation or residential applications. The use of photovoltaic (PV) panels to support the electrical requirements of these pumping systems has been executed globally for a long time. However, introducing optimization sizing techniques to such systems can benefit the end-user by saving money, energy, and time. This paper proposed solar water pumping systems optimum design for Oman. The design, and evaluation have been carried out through intuitive, and numerical methods. Based on hourly meteorological data, the simulation used both HOMER software and numerical method using MATLAB code to find the optimum design. The selected location ambient temperature variance from 12.8 °C to 44.5 °C over the year and maximum insolation is 7.45 kWh/m2/day, respectively. The simulation results found the average energy generated, annual yield factor, and a capacity factor of the proposed system is 2.9 kWh, 2016.66 kWh/kWp, and 22.97%, respectively, for a 0.81 kW water pump, which is encouraging compared with similar studied systems. The capital cost of the system is worth it, and the cost of energy has compared with other systems in the literature. The comparison shows the cost of energy to be in favor of the MATLAB simulation results with around 0.24 USD/kWh. The results show successful operation and performance parameters, along with cost evaluation, which proves that PV water pumping systems are promising in Oman.